The cultivation of rye in marginal Alpine environments: a comparison of the agronomic, technological, health and sanitary traits of local landraces and commercial cultivars - Sardella, Claudia; Capo, Luca; Adamo, Martino; Donna, Matteo; Ravetto Enri, Simone; Vanara, Francesca; Lonati, Michele; Mucciarelli, Marco; Blandino, Massimo (Frontiers in Plant Science, 2023)
Rye is a secondary crop that is characterized by a higher tolerance to climatically less favorable conditions than other cereal species. For this reason, rye was historically used as a fundamental raw material for bread production and as a supply of straw in northern parts of Europe as well as in mountain environments, such as Alpine valleys, where locally adapted landraces have continued to be cultivated over the years. In this study, rye landraces, collected in different valleys in the Northwest Italian Alps, have been selected as the most genetically isolated within their geographical contexts and cultivated in two different marginal Alpine environments. The traits concerning their agronomy, mycotoxin contamination, bioactive content, as well as those concerning their technological and baking quality were assessed to characterize and compare rye landraces with commercial wheat and rye cultivars. Rye cultivars showed the same grain yield level as wheat in both environments. Only the genotype selected from the Maira Valley was characterized by tall and thin culms and a proneness to lodging, thereby resulting in a lower yield capacity. Among the rye cultivars, the hybrid one presented the highest yield potential, but also the highest susceptibility to the occurrence of ergot sclerotia. However, the rye cultivars, especially the landraces, were characterized by higher concentrations of minerals, soluble fibers, and soluble phenolic acids, and thus both their flours and breads had superior antioxidant properties. A 40% substitution of refined wheat flour with whole-grain rye flour led to a higher dough water absorption and a lower stability, thereby resulting in lower loaf volumes and darker products. Agronomically and qualitatively speaking, the rye landraces diverged significantly from the conventional rye cultivars, thus reflecting their genetic distinctiveness. The landrace from the Maira Valley shared a high content in phenolic acids and good antioxidant properties with the one from the Susa Valley, and, when combined with wheat flour, turned out to be the most suitable for bread making. Overall, the results have highlighted the suitability of reintroducing historic rye supply chains, based on the cultivation of local landraces in marginal environments, and the production of value-added bakery goods.